Nanoemulsion and nanoencapsulation of a hydroethanolic extract of Nettle (Urtica dioica) and Wormwood (Artemisia absinthium): comparison of antibacterial and anticancer activity - Rahmani, Zeinab; Karimi, Merat; Saffari, Iman; Mirzaei, Hamed; Nejati, Majid; Sharafati Chaleshtori, Reza (Frontiers in Chemistry, 2024)
Nanoemulsion and nanoencapsulation are attractive novel methods that can be used for incorporating active plant extracts in food preparations and pharmaceutical formulations In the current study, we aimed to investigate the anticancer and antibacterial effects of hydroethanolic extracts of Nettle (NE), Wormwood (WE), and the combination of the two plants (CNWE), as well as their nanoemulsion forms (NN, NW, CNNW) and nanoencapsulation forms (CN, CW, and CCNW). The morphology and structure of the nanoemulsion and nanoencapsulation preparations were assessed utilizing dynamic light scattering (DLS) along with transmission electron microscopy (TEM). The antibacterial activity of the prepared formulations were assessed by determining minimum inhibitory concentration (MIC), zone of inhibition diameter, minimum bactericidal concentration (MBC), along with biofilm growth inhibition against Salmonaella typhimurium and Klebsiella. pneumoniae. The anticancer activity was evaluated via a MTT assay in the colon cancer cell line (HCT116). The nanoemulsion and nanoencapsulation particle size varied between 10 and 50 nm and 60 and 110 nm, respectively. The MIC values were between 11.25 and 95 µg/mL along with MBC values between 11.25 and 190 µg/mL. The highest inhibition of biofilm formation was observed with CCNW against K. pneumoniae (̴ 78.5%) and S. typhimurium (̴ 73%). In descending order, the inhibition of biofilm formation was CCNW > CW > CN > CNNW > NN > NW > CNWE > NE > WE against the tested bacteria. The IC50 values for NE, WE, CNWE, NN, NW, CNNW, CN, CW, and CCNW were determined as 250, 170, 560, 380, 312, 370, 250, 420, and 700 µg/mL, respectively. Exposure to a high concentration of NW resulted in a significantly lower HCT116 viability compared to other groups. Taken together, CNNW, and CCNW showed the highest antibacterial and anticancer activitiy. Nanoemulsion and nanoencapsulation were effective ways to increase the antibacterial and anticancer activity of the extracts and could be used in the food and pharmaceutical industries.